(untitled) (Journal of the College of Languages (JCL), 2019)
This research paper which is entitled “Analysis of Verbs Forms in Sa’eed Faeeq’s Short Story: Cloud in the Sky” deals with the forms of verbs (i.e., kinds of tenses and suffix analysis). It is one of the applied studies. Verbs are basic elements in Turkish sentences. Their function is to state the predicate which is a sentential essential part. Verbs denote sentence construction, action and formal aspects. Forms are added to the base of verbs in the Turkish language giving the verbs their final structures. Such structures are set in a distinct planned way. The verbs used in the Turkish language which are distinguished by one of these forms are known as simple tense verbs. Sait Faik’in ( "Havada Bulut" adlı Hikayesinde Fiil Kiplerinin incelenmesi ) adlı bilimsel çalışmamızda fiil kiplerini (zaman türleri , ekleri , çıkarmaları ve incelemesi) uygulamalı olarak ele aldık. Fiil, Türkçede cümlenin temel öğelerinden biridir. Fiillerin asıl görevi, bir temel cümlenin yüklemi olmaktadır. Yüklem, cümlenin temelidir. Yüklem olmadan cümle kurulamaz. Fiiller, hareketlerine bağlı oluş, kılış ve durumlarıdır. Türkçede fiil köküne kip gelir. Yani fiillerde kip fiilin yapılışını gösterir. Fiilin yapılışı bildirme ve tasarlama biçimlerinde olabilir. Türkçede kullanılan fiillerin bu kiplerden biriyle çekimlenmiş biçimine basit zamanlı fiil denir.